GOALS AND OBJECTIVES OF TEACHERS IN A CLASSROOM (Ustozlar uchun, 2025)
This article explores the main goals and objectives of teachers in a classroom setting. It examines academic, instructional, social, emotional, and professional aims that guide effective teaching. The article highlights the importance of clear lesson planning, classroom management, assessment, and the integration of technology. It also emphasizes the teacher’s role in fostering critical thinking, motivation, cooperation, and lifelong learning. Overall, the paper provides a comprehensive overview of how teachers contribute to students’ holistic development.